GLORIA BETWEEN TWO CULTURES: IDENTITY NEGOTIATION IN MODERN FAMILY (2009) - Asyari, Khafidatul Afifah; Saraswati, Ayu (Universitas Negeri Surabaya, 2026)
This study examines the negotiation of cultural identity through the character of Gloria in Modern Family Season 1 (2009). As a Colombian immigrant living within an American family structure, Gloria represents the complexities of multicultural identity in everyday domestic life. Drawing on Homi K. Bhabha’s concept of the Third Space and intercultural communication theory proposed by Judith Martin and Thomas Nakayama, this study analyzes how identity is negotiated through language, family roles, traditions, and class relations. Using a qualitative descriptive method with thematic analysis, data were collected from selected episodes in Season One. The findings reveal that Gloria neither fully assimilates into American culture nor entirely preserves a fixed Colombian identity. Instead, she constructs a hybrid identity through adaptation, resistance, and everyday cultural preservation. This study demonstrates that television sitcoms can represent multicultural identity as fluid, relational, and continuously negotiated.